Lidocaine as Endotracheal Tube Cuff Inflating Agent - Ali, Nadeem Parvez; Tauhid-ul-Mulck, Md; Noor, Mahbub; Mollick, Md Torab; Ahmed, Masud; Chowdhury, Md Rezaul Alam (Journal of Armed Forces Medical College, Bangladesh, 1970)
A prospective study was carried on 120 patients undergoing surgical operations lasting less than 90 minutes. The incidence of postoperative sore throat, dysphasia and hoarseness of voice with 2% lidocaine (Group L) as endotracheal cuff inflating agent was compared with that with distilled water (Group D) and air (Group A). Seventy two percent of lidocaine group in comparison to 60% distilled water group and 37% air group experienced none of the above complications during the entire study period. Only 5% in lidocaine group had sore throat after 22-24 hours compared to 20% in the distilled water group and 45% in the air group. Twenty three percent complained of dysphasia in both lidocaine and distilled water group after 1-3 hours compared to 45% in air group. After 22-24 hours it completely resolved in lidocaine group compared to 20% persisting in the other two groups. Twenty three percent complained of hoarseness in lidocaine group as compared to 35% and 55% in distilled water and air groups respectively after 1-3 hours. This completely resolved in lidocaine group but persisted in 20% and 45% in the distilled water and air group respectively after 22-24 hours. The results showed an advantage in using lidocaine as an endotracheal tube cuff inflating agent in reducing postoperative sore throat, dysphasia and hoarseness in comparison to distilled water and air. Key Words: Lidocain, Endotracheal tube (ETT) cuff inflating agent.   doi: 10.3329/jafmc.v5i1.2847 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.25-28